(untitled) (Research, Society and Development, 2021)
The Ti6Al4V alloy is usually employed as a biomaterial, however, when in use, exhibits a few drawbacks such as corrosion, caused by the release of aluminum and vanadium ions besides the bioinert behavior. Bioactive coatings offer a barrier effect and bioactivity, promoting biocompatibility and osseointegration processes. The present work aims to study the biocompatibility behavior of a bioglass-containing silane film deposited on a titanium alloy (Ti6Al4V) substrate. The effect of the surface roughness of the metallic substrate was also evaluated. Film/substrate systems were characterized as their morphological, chemical, physical, electrochemical behavior, and cell cytotoxicity and cell viability. The main results pointed out that silane films augment corrosion resistance of titanium alloy substrates. The biological results indicated a growth of osteoblast cells (MG-63), for all the test conditions. The bioglass film deposited on the ground substrate exhibits the highest cell density.